2010
DOI: 10.1139/g10-050
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously accounting for population structure, genotype by environment interaction, and spatial variation in marker–trait associations in sugarcaneThis article is one of a selection of papers from the conference “Exploiting Genome-wide Association in Oilseed Brassicas: a model for genetic improvement of major OECD crops for sustainable farming”.

Abstract: Few association mapping studies have simultaneously accounted for population structure, genotype by environment interaction (GEI), and spatial variation. In this sugarcane association mapping study we tested models accounting for these factors and identified the impact that each model component had on the list of markers declared as being significantly associated with traits. About 480 genotypes were evaluated for cane yield and sugar content at three sites and scored with DArT markers. A mixed model was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 34 publications
(51 reference statements)
1
20
0
Order By: Relevance
“…GWA and genomic prediction studies that used phenotypic data spanning multiple continents are rare, with notable exceptions being a few studies in wheat (Crossa et al, 2014(Crossa et al, , 2007. However, such broad sampling of environments can enable the identification of SNPs that are broadly useful for improving breeding values across environments (Wei et al, 2010) and improve genomic prediction accuracy via the use of phenotypes from correlated environments (Crossa et al, 2014;Spindel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…GWA and genomic prediction studies that used phenotypic data spanning multiple continents are rare, with notable exceptions being a few studies in wheat (Crossa et al, 2014(Crossa et al, , 2007. However, such broad sampling of environments can enable the identification of SNPs that are broadly useful for improving breeding values across environments (Wei et al, 2010) and improve genomic prediction accuracy via the use of phenotypes from correlated environments (Crossa et al, 2014;Spindel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding genome complexity, several studies have applied association mapping to sugarcane. Using 1,209 polymorphic markers (AFLP and SSR), Wei et al (2006) detected associations with resistance to four diseases in a collection of 154 cultivars and later on they identified DArT markers related to cane yield and sugar content traits on a sample of 480 genotypes (Wei et al 2010). These studies confirmed the potential of genome-wide association mapping in the polyploid context of sugarcane.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances [10][16], biotechnology for sugarcane analysis is less advanced than that for other economically important crops. For example, compared with sorghum, maize, and rice, sugarcane does not have a draft genome sequence available or a well-annotated transcriptome.…”
Section: Introductionmentioning
confidence: 99%